Meningkatkan Kreativitas Kinerja Karyawan Hotel: Dukungan Kepribadian, Emosional, dan Lingkungan - Aurilia Triani Aryaningtyas; Aletta Dewi Maria Th; Renny Aprilliyani (J-MAS (Jurnal Manajemen dan Sains), 2020)
This study examines the effect of proactive personality, emotional intelligence, and work environment on employee performance creativity using data 200 employees of star hotels in Semarang. The results showed that proactive personality, emotional intelligence, and work environment had a positive and significant effect on employee performance creativity. The theoretical implications of the research results support existing theories and research, while managerial implications suggest that organizations / hotels consider proactive personality, emotional intelligence, and work environment as important factors that encourage employees to work creatively in order to improve their performance.